Consumer Attitudes Toward Imported and Local Produce in Indonesia: The Role of Country of Origin and Perception in Shaping Preferences: Consumer Attitudes Toward Imported and Local Produce in Indonesia - Simanjuntak, Megawati (Benefit: Jurnal Manajemen dan Bisnis, 2025)
Imported fruits and vegetables in Indonesia offer consumers a wider variety of choices but negatively impact local farmers who struggle to compete. This research aimed to 1) analyze differences in attitudes and preferences for fruits and vegetables between unexposed and exposed groups; 2) examine the influence of country of origin and attitude on preferences; and 3) explore the effect of perception and attitude on preferences. The study employed a survey and quasi-experimental method with 120 housewives, analyzed using an independent t-test and SmartPLS. The findings revealed significant differences in attitudes between the unexposed and exposed groups. Country of origin positively influenced attitudes in the experimental method, while survey results showed attitudes significantly affected preferences. Recommendations include government measures to limit imports of commodities available domestically, improve local produce quality, and mandate labeling of fruit and vegetable origins. Business actors should provide clear import or local information on produce. Additionally, the Ministry of Trade should promote programs fostering positive attitudes toward local produce to increase consumer preference. Future research could explore variables like experience, knowledge, lifestyle, and taste attributes to better understand factors influencing attitudes and preferences.